The Human Performance Technology Activities through Learning Management System-based Training - Sudarmika, Putu; Wirianti, Ken; Sudatha, I Gde Wawan; Premananda, I Made Sathya (Universitas Pendidikan Ganesha, 2025)
The evaluation of employee performance following technology-based training in health institutions remains a challenge, particularly in developing comprehensive assessment strategies from both employee and managerial perspectives. This study aims to analyze the relationship between the application of a Learning Management System (LMS)-based learning model and employee performance. A mixed-method study design was applied. In the first phase, quantitative data were collected through an online questionnaire, which had previously been tested for validity (r > 0.361) and reliability (Cronbach's Alpha = 0.90). A total of 400 questionnaires were distributed, with 360 respondents meeting the inclusion criteria (response rate 96.7%). The second phase employed a Focus Group Discussion (FGD) involving 20 managers to explore and deepen the quantitative findings. Data were analyzed using Pearson’s correlation test to examine the relationship between variables. The results indicated a significant relationship between the acceptance of LMS-based learning and employee performance (p < 0.05; R = 0.615). The FGD findings revealed differing perceptions, although LMS-based learning was perceived to offer advantages in terms of time flexibility and enhanced employee self-confidence. This study concludes that integrating LMS in employee training positively impacts performance improvement, implying the need for its implementation through structured learning needs analysis, LMS-based content development, and continuous performance achievement evaluation.